Mindfulness for young adults : tools to thrive in school and life - Yaron Weston, Linda (New York, NY : Routledge, 2021)
"Mindfulness for Young Adults: Tools to Thrive in School and Life is an interactive experience designed to enhance mindful awareness in life and to aid in teaching and learning the principles and practice of mindfulness. Blending theory, research, and practice to offer a comprehensive program for young adults to build well-being tools, each of the book's five modules includes engaging information, techniques, meditations, and activities designed to deepen understanding and application of mindfulness. Voices of college students in their mindfulness journeys are shared alongside those in the fields of psychology, yoga, literature, education, and history for an integrative study of well-being practices. In addition to the reflection and meditation activities found at the end of each module, the text also features a "resources" section complete with a mock exam, tips for course design, and resources for further study. Designed for both students and instructors, this workbook can be used independently or in the classroom as either a textbook to an introductory mindfulness course or as a supplement for teaching well-being practices in any discipline"--
OCLC-licensed vendor bibliographic record.
Keywords: Mindfulness-based cognitive therapy; Mindfulness (Psychology)